The Relationship Between Participation in Elderly Gymnastics and Hypertension Incidence at Kalirejo Public Health Center - Andriani, Rita Oktavia; Yulianti, Eka; Sari, Nova Nurwinda (Genius Journal, 2025)
Introduction: Elderly gymnastics is a structured physical activity designed to enhance the functional health of older adults. As hypertension remains a leading cause of outpatient visits at Kalirejo Health Center, Negeri Katon District, the effectiveness of elderly gymnastics as a preventive strategy warrants investigation. Objective: This study aimed to examine the relationship between participation in elderly gymnastics and the incidence of hypertension among elderly individuals at the Kalirejo Health Center in 2024. Method: This research used a quantitative approach with a descriptive correlational method and cross-sectional design. The sample consisted of 80 elderly respondents selected using the Slovin formula. study used an observation sheet as a data collection tool where the data collected was a recapitulation of the attendance list of elderly gymnastics participants and the Community Health Center medical records (patient visit records).Data were analyzed using a chi-square statistical test. Result: Findings showed that most respondents who actively participated in elderly gymnastics did not have hypertension. Statistical analysis yielded a p-value of 0.020, indicating a significant relationship between the level of participation and the incidence of hypertension. Conclusion: There is a significant relationship between elderly gymnastics participation and the incidence of hypertension. Active involvement in regular physical activity such as elderly gymnastics may help reduce hypertension risk. Future research should explore factors influencing elderly participation to enhance program effectiveness.